Medical treatment of endometriosis-related pain. (August 2018) - Vercellini, Paolo; Buggio, Laura; Frattaruolo, Maria Pina; Borghi, Alessandra; Dridi, Dhouha; Somigliana, Edgardo
Abstract: Available medical treatments for symptomatic endometriosis act by inhibiting ovulation, reducing serum oestradiol levels, and suppressing uterine blood flows. For this, several drugs can be used with a similar magnitude of effect, in terms of pain relief, independently of the mechanism of action. Conversely, safety, tolerability, and cost differ. Medications for endometriosis can be categorized into low-cost drugs including oral contraceptives (OCs) and most progestogens, and high-cost drugs including dienogest and GnRH agonists. As the individual response to different drugs is variable, a stepwise approach is suggested, starting with OCs or low-cost progestogens, and stepping up to high-cost drugs only in case of inefficacy or intolerance. OCs may be used in women with dysmenorrhea as their main complaint, and when only superficial peritoneal implants or ovarian endometriomas <5 cm are present, while progestogens should be preferred in women with severe deep dyspareunia and when infiltrating lesions are identified. Highlights: Endometriosis is a chronic disorder requiring long-term adherence to treatment. Individual response to drugs is variable, and a stepwise approach is suggested. Progestogens should be selected in case of deep lesions and severe deep dyspareunia.